Strengthening Maqāṣid al-Sharī’ah Values in Halal Traceability: Evidence and Analysis of Block Chain Based on Halal Supply Chain Applications - Nashirudin, Muh.; Ramadhan; Almira Keumala Ulfah (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2024)
Halal traceability is one of the government's focus in developing the halal industry. By adopting a blockchain system, halal traceability is undoubtedly transparent. However, this transparency also needs to be analyzed using maqāṣid al-sharī'ah. This analysis is used to analyze the extent of the application of maqāṣid al-sharī'ah values in halal traceability. The results of the study state that the application of halal traceability has fulfilled the elements of maqāṣid al-sharī'ah, such as transparency, accountability, responsibility, and justice. Therefore, the blockchain-based halal traceability application model is appropriate and relevant to Islamic values.